2012
DOI: 10.1111/j.1745-7599.2012.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of postpartum depression among Hispanic immigrant women

Abstract: Given that a large number of Hispanic women do not return for postpartum appointments, along with the high rates of PPD symptoms, it is strongly recommended that healthcare providers implement universal screening for all Hispanic women in pregnancy and across the first postpartum year to ensure prompt diagnosis and culturally appropriate treatment. Further research is needed to assess the cultural components of PPD and to determine if the prevalence is consistent in other community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 27 publications
8
82
0
Order By: Relevance
“…15,16,18,21,26,32 Scales such as PDSS, MINI, Hamilton depression scale and SRQ25 have been used rarely. 10,27,29,31 The major drawback of the EPDS scale is its inability to assess antepartum depression as it is specifically designed for postpartum depression. Thus we have also used in addition to EPDS the Becks Depression Inventory which could be used in both the antepartum and postpartum period and thus help in assessment of true incidence and prevalence of postpartum depression as has been used by other authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16,18,21,26,32 Scales such as PDSS, MINI, Hamilton depression scale and SRQ25 have been used rarely. 10,27,29,31 The major drawback of the EPDS scale is its inability to assess antepartum depression as it is specifically designed for postpartum depression. Thus we have also used in addition to EPDS the Becks Depression Inventory which could be used in both the antepartum and postpartum period and thus help in assessment of true incidence and prevalence of postpartum depression as has been used by other authors.…”
Section: Resultsmentioning
confidence: 99%
“…1,6,8, 12,15,19.20,23,33 Most authors have resorted to a single cross sectional survey in the postpartum period. 1,[5][6][7][8][9][10][11]14,[16][17][18][19][20][21][22][23][24]26,27,29,[32][33][34] The essential flaw in a single time point evaluation in the postpartum period is over estimating the prevalence as it undermines the importance of, exclusion of cases that may have also pre existing depression in the antepartum period which does not necessarily classify as postpartum depression. Therefore the incidence of the disease is probably a more important estimate than point prevalence as was estimated in most studies.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the incidence worldwide is supposed to be 10-20% [8]. In Hispanic women the prevalence of significant symptoms of PPD was found to be much higher (54.2%) [9].…”
Section: Methods and Samplesmentioning
confidence: 99%
“…Literature revealed between 52% and 56% incidence of positive PPD screens for high-risk women when screened between 2 and 3 weeks postpartum (Chaudron et al, 2010;Lucero, Beckstrand, Callister, & Sanchez-Birkhead, 2012;Reck, Stehle, Reinig, & Mundt, 2009); therefore, the benchmark deemed appropriate for positive screens was 50%. Significant variation on the prevalence of postpartum suicidal ideation is reflected in the literature, ranging from 22% to 62.5% of women screening positive (Le, Perry, & Ortiz, 2010;Lucero et al, 2012;Sit, Seltman, & Wisner, 2011), and 3.2% of all women screened for PPD in another study (Wisner et al, 2013); therefore, the benchmark deemed appropriate for women identified with postpartum suicidal ideation was 3%.…”
Section: Key Measures For Improvementmentioning
confidence: 99%